Pelatihan Membuat Media Pembelajaran Interaktif Kepada Guru SMKN 8 Pekanbaru Menggunakan Canva - Hardianto, Roki; Wirdahchoiriah, Wirdahchoiriah; Ohara, Muammar Revnu (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2023)
The rapid development of information technology has made the order of life change drastically. The development of social media is a branch of the development of information technology into an extraordinary phenomenon. Content creators have sprung up from both professionals and amateurs who are still in the curious stage. SMKN 8 Pekanbaru is one of the pioneer schools that has a major that is close to the development of content creators. Training activities make content creators necessary for students as an initial provision. Community Service activities have been carried out at the school on December 14, 2022 for students and have succeeded in increasing student understanding from the results of the questionnaire measurements provided. Students successfully create social media content using https://www.canva.com/. The output of activities is in the form of news of activities published on news portals and scientific journals published in national community service journals.